MENGUKUR NILAI KENYAMANAN TERMAL PADA MOBIL DENGAN KACA FILM BERTEKNOLOGI (ENGINEERED WINDOW FILM) - Ruliandini, Rizky (AME (Aplikasi Mekanika dan Energi): Jurnal Ilmiah Teknik Mesin, 2016)
When a car is parked during daylight, later it is found that the car will be very hot and need some times from start up until reach the steady state condition or the thermal comfort achieved. This study presents a thermal comfort’s theoretical measurements based on the experiment on a car which using engineered window film. The experiments were performed in order to determine the heat and mass transfer between the body and the environment (car compartment). During experiment, the changed temperature of five body segment (forehead, left arm, right arm, hand and back); car compartment’s temperature; relative humidity and air velocity were measured. Based on the heat balance equation on human, the changes in convective, radiative, conductive, evaporative heat loss; heat loss from respiration; skin wittedness and thermal comfort indices were calculated. As a result, in the first 30 minutes, the film able to reduce compartment temperature until 5.2° C, it makes the thermal comfort achieved in less than 10 minutes.